Suspected case of rabies in a patient immunized with anti-rabies vaccine - Vrunda T. Parikh; Sapna D. Gupta; Supriya D. Malhotra (International Journal Of Community Medicine And Public Health, 2026)
Rabies remains a major public health threat, especially in developing countries like India, where stray dogs account for 99% of human cases. The disease is almost always fatal once symptoms appear, with death occurring within days. Despite highly effective pre- and post-exposure prophylaxis (PEP) with WHO-recommended vaccines, challenges like occasional vaccine failure persist. In India, rabies causes approximately 20,000 deaths annually. This case highlights a suspected rabies infection that developed despite receiving PEP, exploring potential reasons for the failure. This case emphasizes the necessity for a deeper understanding of factors that may lead to vaccine ineffectiveness. It also underscores the critical role of administering rabies immunoglobulin (RIG), proper wound care and following established guidelines.